“NOWADAYS THEY SAY … ”: ADOLESCENT PEER COUNSELLORS’ APPRECIATION OF CHANGES IN THE CONSTRUCTION OF MASCULINITY - Davies, Nicholas; Eagle, Gillian (PINS-Psychology in Society, 2025)
The article describes findings from a research study conducted into young South African men’s understandings of masculinity. The study was part of a broader project aimed at investigating how young men or boys in South Africa view masculinity, including dominant or hegemonic forms and alternatives to these constructions. Given concerns about a “crisis in masculinity” and social problems associated with the enactment of masculinity, the researchers were interested in how young boys seem to position themselves with respect to a masculine gender identity. Three focus groups were held with volunteer peer counsellors who were invited to start the groups by talking about photographs they had taken to represent their “life as a boy/young man” in contemporary South Africa. The main focus of the discussion is on aspects of the data that appear to reflect an appreciation of the fluidity or malleability of masculinity. Three key themes are addressed, that is, emotionality, homosexuality and occupational sex roles. In addition, some parts of their discussion about becoming counsellors and their concerns about reconciling this identity with their sense of themselves as masculine is also elaborated. The discussion suggests that these boys appreciate challenges to traditional constructions of masculinity and that in their conversation they both accept this and attempt to defend aspects of conventional or previously dominant versions. It is proposed that their conversational work suggests that there is some awareness of change, some anxiety associated with this, and some strategizing to reconcile a range of differing positions on masculinity. The sense of some openness to transforming aspects of masculinity is seen as hopeful, even if this is to some extent a product of these boys’ predominantly middle class upbringing.